Developing Flashcards and the Manual Book for Teaching English Vocabulary for Young Learners in Singaraja - Taharyanti, Gusti Ayu Putu (Universitas Pendidikan Ganesha, 2017)
This was a Research and Development study which intended to develop flashcards and manual book as teaching media for teaching English vocabulary for young learner in Singaraja. The subjects of this study were five English teachers in Singaraja. They were SDN 1 Baktiseraga, SDN 1 Banjar Bali, SDN 2 Banyuasri, SDN 2 Pemaron, and SDN 3 Kampung Baru. This study used design model proposed by Hannafin and Peck (1988). The instruments used in this study were interview guide, questionnaires for teachers and students, and the evaluation sheet. The data gathered was analyzed qualitatively and quantitatively. The result showed that teachers actually did not have any representative flashcards. The flashcards developed in this study covered 11 topics of noun and they were provided by manual book to support the implementation of the develop flashcards. The quality of the flashcards and the manual book got score almost 5 (highest score) from experts, which categorized to the excellent category. From the aforementioned result, it can be concluded that the teachers did not have any representative flashcards, therefore the development of flashcards which contained 11 topics of noun was conducted, and was supported by manual book in which their qualities were excellent.Â